Sickness absence and associations with sociodemographic factors, health risk behaviours, occupational stressors and adverse mental health in 40,343 UK police employees - S. Parkes; P. Irizar; N. Greenberg; S. Wessely; N. T. Fear; M. Hotopf; S. A. M. Stevelink (Cambridge University Press, 2024)
Abstract Aims Police employees may experience high levels of stress due to the challenging nature of their work which can then lead to sickness absence. To date, there has been limited research on sickness absence in the police. This exploratory analysis investigated sickness absence in UK police employees. Methods Secondary data analyses were conducted using data from the Airwave Health Monitoring Study (2006-2015). Past year sickness absence was self-reported and categorised as none, low (1-5 days), moderate (6-19 days) and long-term sickness absence (LTSA, 20 or more days). Descriptive statistics and multinomial logistic regressions were used to examine sickness absence and exploratory associations with sociodemographic factors, occupational stressors, health risk behaviours, and mental health outcomes, controlling for rank, gender and age. Results From a sample of 40,343 police staff and police officers, forty-six per cent had no sickness absence within the previous year, 33% had a low amount, 13% a moderate amount and 8% were on LTSA. The groups that were more likely to take sick leave were women, non-uniformed police staff, divorced or separated, smokers and those with three or more general practitioner consultations in the past year, poorer mental health, low job satisfaction and high job strain. Conclusions The study highlights the groups of police employees who may be more likely to take sick leave and is unique in its use of a large cohort of police employees. The findings emphasise the importance of considering possible modifiable factors that may contribute to sickness absence in UK police forces.